Optimizing The Implementation Of Cyber Patrol Against The Spread Of Child Sexual Exploitation Pornography - Fibriana, Ainur; Harefa, Beniharmoni (UNIVERSITAS PAKUAN, 2025)
AbstractTechnological advancement has led to unintended consequences, including cybercrime. One of the most pressing threats is online pornography, which poses serious harm—especially to children as a vulnerable group. In response, child protection efforts must be strengthened by all stakeholders to uphold the best interests of the child. This study examines the role of cyber patrols in combating the spread of child pornography and analyzes ways to enhance their implementation. Using a normative legal method with statutory and conceptual approaches, the research finds that cyber patrols play a vital role in ensuring children’s right to safety in the digital environment. However, in practice, several challenges hinder their effectiveness. These include limited human resources with technical expertise and weak inter-agency coordination, both of which reduce the efficiency of monitoring and removing harmful content. Strengthening collaboration and capacity is essential for optimizing cyber patrols in protecting children online. Keywords : Cyber Patrol; Child Pornography; Optimalitation